Um problema de sequenciamento em máquinas paralelas não-relacionadas com tempos de preparação dependentes de máquina e da sequência: modelos e algoritmos exato. - Pedro Leite Rocha (2006)
A scheduling problem with unrelated parallel machines, sequence andmachine dependent setup times, due dates and weighted jobs isconsidered in this work. Two mixed integer programing (MIP) modelsbased on classic strategies from the literature are evaluated. ABranch-and-Bound algorithm (B&B) is developed and a solution providedby the metaheuristic GRASP is used as an upper bound. We also propose a set of instances for this type of problem. Computational experiments are carried out in several types of tests, where the algorithmperforms well on instances with up to 30 jobs. Finally, conclusionsand directions for future work are presented.